NanoCAGE analysis of the mouse olfactory epithelium identifies the expression of vomeronasal receptors and of proximal LINE elements - Pascarella, Giovanni; Lazarevic, Dejan; Plessy, Charles; Bertin, Nicolas; Akalin, Altuna; Vlachouli, Christina; Simone, Roberto; Faulkner, Geoff; Zucchelli, Silvia; Kawai, Jun; Daub, Carsten O.; Hayashizaki, Yoshihide; et al. (Frontiers in Cellular Neuroscience, 2014)
By coupling laser capture microdissection to nanoCAGE technology and next-generation sequencing we have identified the genome-wide collection of active promoters in the mouse Main Olfactory Epithelium (MOE). Transcription start sites (TSSs) for the large majority of Olfactory Receptors (ORs) have been previously mapped increasing our understanding of their promoter architecture. Here we show that in our nanoCAGE libraries of the mouse MOE we detect a large number of tags mapped in loci hosting Type-1 and Type-2 Vomeronasal Receptors genes (V1Rs and V2Rs). These loci also show a massive expression of Long Interspersed Nuclear Elements (LINEs). We have validated the expression of selected receptors detected by nanoCAGE with in situ hybridization, RT-PCR and qRT-PCR. This work extends the repertory of receptors capable of sensing chemical signals in the MOE, suggesting intriguing interplays between MOE and VNO for pheromone processing. It positions transcribed LINEs as candidate regulatory RNAs for VRs expression.